A microscopic view on the Mott transition in chromium-doped V2O3 - Lupi, S.; Baldassarre, Leonetta; Mansart, B.; Perucchi, A.; Barinov, Alexey; Dudin, Pavel; Papalazarou, E.; Rodolakis, Fanny; Rueff, J. -P.; Itie, J. -P.; Ravy, Sylvain; Nicoletti, D.; et al. (Nature Communications, 2010)
V2O3 is the prototype system for the Mott transition, one of the most fundamental phenomena of electronic correlation. Temperature, doping or pressure induce a metal-to-insulator transition (MIT) between a paramagnetic metal (PM) and a paramagnetic insulator. This or related MITs have a high technological potential, among others, for intelligent windows and field effect transistors. However the spatial scale on which such transitions develop is not known in spite of their importance for research and applications. Here we unveil for the first time the MIT in Cr-doped V2O3 with submicron lateral resolution: with decreasing temperature, microscopic domains become metallic and coexist with an insulating background. This explains why the associated PM phase is actually a poor metal. The phase separation can be associated with a thermodynamic instability near the transition. This instability is reduced by pressure, that promotes a genuine Mott transition to an eventually homogeneous metallic state.
CRIS-Team WoS Importer:2020-02-19

A new benchmark of soft X-ray transition energies of Ne , CO 2 , and SF 6 : paving a pathway towards ppm accuracy - Stierhof, Jakob; Kühn, S.; Winter, Mirko; Micke, P.; Steinbrügge, R.; Shah, C.; Hell, N.; Bissinger, Matthias; Hirsch, Maria; Ballhausen, Ralf; Lang, Melanie; Gräfe, Christina; et al. (European Physical Journal D, 2022)
Abstract: A key requirement for the correct interpretation of high-resolution X-ray spectra is that transition energies are known with high accuracy and precision. We investigate the K-shell features of Ne , CO 2, and SF 6 gases, by measuring their photo ion-yield spectra at the BESSY II synchrotron facility simultaneously with the 1s–np fluorescence emission of He-like ions produced in the Polar-X EBIT. Accurate ab initio calculations of transitions in these ions provide the basis of the calibration. While the CO 2 result agrees well with previous measurements, the SF 6 spectrum appears shifted by ∼ 0.5 eV, about twice the uncertainty of the earlier results. Our result for Ne shows a large departure from earlier results, but may suffer from larger systematic effects than our other measurements. The molecular spectra agree well with our results of time-dependent density functional theory. We find that the statistical uncertainty allows calibrations in the desired range of 1–10 meV, however, systematic contributions still limit the uncertainty to ∼ 40–100 meV, mainly due to the temporal stability of the monochromator energy scale. Combining our absolute calibration technique with a relative energy calibration technique such as photoelectron energy spectroscopy will be necessary to realize its full potential of achieving uncertainties as low as 1–10 meV. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-03-11

Atomic and itinerant effects at the transition-metal x-ray absorption K pre-edge exemplified in the case of V2O3 - Hansmann, Philipp; Haverkort, M. W.; Toschi, Alessandro; Sangiovanni, Giorgio; Rodolakis, Fanny; Rueff, J. P.; Marsi, Marino; Held, Karsten (Physical Review B, 2012)
X-ray absorption spectroscopy is a well-established tool for obtaining information about orbital and spin degrees of freedom in transition-metal and rare-earth compounds. For this purpose usually the dipole transitions of the L (2p to 3d) and M (3d to 4f) edges are employed, whereas higher order transitions such as quadrupolar 1s to 3d in the K edge are rarely studied in that respect. This is due to the fact that usually such quadrupolar transitions are overshadowed by dipole-allowed 1s to 4p transitions and, hence, are visible only as minor features in the pre-edge region. Nonetheless, these features carry a lot of valuable information, similar to the dipole L-edge transition, which is not accessible in experiments under pressure due to the absorption of the diamond anvil pressure cell. We recently performed a theoretical and experimental analysis of such a situation for the metal-insulator transition of (V(1-x)Crx)(2)O-3. Since the importance of the orbital degrees of freedom in this transition is widely accepted, a thorough understanding of quadrupole transitions of the vanadium K pre-edge provides crucial information about the underlying physics. Moreover, the lack of inversion symmetry at the vanadium site leads to on-site mixing of vanadium 3d and 4p states and related quantum mechanical interferences between dipole and quadrupole transitions. Here we present a theoretical analysis of experimental high-resolution x-ray absorption spectroscopy at the V K pre-edge measured in partial fluorescence yield mode for single crystals. We carried out density functional as well as configuration interaction calculations in order to capture effects coming from both itinerant and atomic limits.
CRIS-Team WoS Importer:2020-02-19

Band Alignment and Charge Transfer in Complex Oxide Interfaces - Zhong, Zhicheng; Hansmann, Philipp (Physical Review X, 2017)
The synthesis of transition metal heterostructures is currently one of the most vivid fields in the design of novel functional materials. In this paper, we propose a simple scheme to predict band alignment and charge transfer in complex oxide interfaces. For semiconductor heterostructures, band-alignment rules like the well-known Anderson or Schottky-Mott rule are based on comparison of the work function or electron affinity of the bulk components. This scheme breaks down for oxides because of the invalidity of a single work-function approximation as recently shown in [Phys. Rev. B 93, 235116 (2016); Adv. Funct. Mater. 26, 5471 (2016)]. Here, we propose a new scheme that is built on a continuity condition of valence states originating in the compounds' shared network of oxygen. It allows for the prediction of sign and relative amplitude of the intrinsic charge transfer, taking as input only information about the bulk properties of the components. We support our claims by numerical density functional theory simulations as well as (where available) experimental evidence. Specific applications include (i) controlled doping of SrTiO3 layers with the use of 4d and 5d transition metal oxides and (ii) the control of magnetic ordering in manganites through tuned charge transfer.
CRIS-Team WoS Importer:2020-02-19

Bands, resonances, edge singularities and excitons in core level spectroscopy investigated within the dynamical mean-field theory - Haverkort, M. W.; Sangiovanni, Giorgio; Hansmann, Philipp; Toschi, Alessandro; Lu, Yi; Macke, S. (EPL - Europhysics Letters, 2014)
Using a recently developed impurity solver we exemplify how dynamical mean-field theory captures band excitations, resonances, edge singularities and excitons in core level x-ray absorption spectroscopy (XAS) and core level photo electron spectroscopy (cPES) on metals, correlated metals and Mott insulators. Comparing XAS at different values of the core-valence interaction shows how the quasiparticle peak in the absence of core-valence interactions evolves into a resonance of similar shape, but different origin. Whereas XAS is rather insensitive to the metal insulator transition, cPES can be used, due to nonlocal screening, to measure the amount of local charge fluctuation. Copyright (C) EPLA, 2014
CRIS-Team WoS Importer:2020-02-19

Charge-transfer energy in iridates: A hard x-ray photoelectron spectroscopy study - Takegami, D.; Kasinathan, D.; Wolff, K. K.; Altendorf, S. G.; Chang, C. F.; Hoefer, K.; Melendez-Sans, A.; Utsumi, Y.; Meneghin, F.; Ha, T. D.; Yen, C. H.; Chen, K.; et al. (Physical Review B, 2020)
We have investigated the electronic structure of iridates in the double perovskite crystal structure containing either Ir4+ or Ir5+ using hard x-ray photoelectron spectroscopy. The experimental valence band spectra can be well reproduced using tight-binding calculations including only the Ir 5d, O 2p, and O 2s orbitals with parameters based on the downfolding of the density-functional band structure results. We found that, regardless of the A and B cations, the A(2)BIrO(6) iridates have essentially zero O 2p to Ir 5d charge-transfer energies. Hence double perovskite iridates turn out to be extremely covalent systems with the consequence being that the magnetic exchange interactions become very long ranged, thereby hampering the materialization of the long-sought Kitaev physics. Nevertheless, it still would be possible to realize a spin-liquid system using the iridates with a proper tuning of the various competing exchange interactions.
CRIS-Team WoS Importer:2020-07-24

Chiral d-wave superconductivity in a triangular surface lattice mediated by long-range interaction - Cao, Xiaodong; Ayral, Thomas; Zhong, Zhicheng; Parcollet, Olivier; Manske, Dirk; Hansmann, Philipp (Physical Review B, 2018)
Adatom systems on the Si(111) surface have recently attracted an increasing attention as strongly correlated systems with a rich phase diagram. We study these materials by a single band model on the triangular lattice, including 1/r long-range interaction. Employing the recently proposed TRILEX method, we find an unconventional superconducting phase of chiral d-wave symmetry in hole-doped systems. Contrary to usual scenarios where charge and spin fluctuations are seen to compete, here the superconductivity is driven simultaneously by both charge and spin fluctuations and crucially relies on the presence of the long-range tail of the interaction. We provide an analysis of the relevant collective bosonic modes and predict how a cumulative charge and spin paring mechanism leads to superconductivity in doped silicon adatom materials.
CRIS-Team WoS Importer:2020-02-19

Complex magnetic order in nickelate slabs - Hepting, Matthias; Green, R. J.; Zhong, Zhicheng; Bluschke, M.; Suyolcu, Y. E.; Macke, S.; Frano, A.; Catalano, Sara; Gibert, Marta; Sutarto, R.; He, Feizhou; Cristiani, G.; et al. (Nature Physics, 2018)
Magnetic ordering phenomena have a profound influence on the macroscopic properties of correlated-electron materials, but their realistic prediction remains a formidable challenge. An archetypical example is the ternary nickel oxide system RNiO3 (R = rare earth), where the period-four magnetic order with proposals of collinear and non-collinear structures and the amplitude of magnetic moments on different Ni sublattices have been subjects of debate for decades(1-6). Here we introduce an elementary model system-NdNiO3 slabs embedded in a non-magnetic NdGaO3 matrix-and use polarized resonant X-ray scattering (RXS) to show that both collinear and non-collinear magnetic structures can be realized, depending on the slab thickness. The crossover between both spin structures is correctly predicted by density functional theory and can be qualitatively understood in a low-energy spin model. We further demonstrate that the amplitude ratio of magnetic moments in neighbouring NiO6 octahedra can be accurately determined by RXS in combination with a correlated double cluster model. Targeted synthesis of model systems with controlled thickness and synergistic application of polarized RXS and ab initio theory thus provide new perspectives for research on complex magnetism, in analogy to two-dimensional materials created by exfoliation(7).
CRIS-Team WoS Importer:2020-02-19

Control of the metal-insulator transition in NdNiO3 thin films through the interplay between structural and electronic properties - Suyolcu, Y. E.; Fürsich, K.; Hepting, M.; Zhong, Z.; Lu, Y.; Wang, Y.; Christiani, G.; Logvenov, G.; Hansmann, Philipp; Minola, M.; Keimer, B.; Van Aken, P. A.; et al. (Physical Review Materials, 2021)
Heteroepitaxy offers a new type of control mechanism for the crystal structure, the electronic correlations, and thus the functional properties of transition-metal oxides. Here we combine electrical transport measurements, high-resolution scanning transmission electron microscopy (STEM), and density functional theory (DFT) to investigate the evolution of the metal-to-insulator transition (MIT) in NdNiO3 films as a function of film thickness and NdGaO3 substrate crystallographic orientation. We find that for two different substrate facets, orthorhombic (101) and (011), modifications of the NiO6 octahedral network are key for tuning the transition temperature TMIT over a wide temperature range. A comparison of films of identical thickness reveals that growth on [101]-oriented substrates generally results in a higher TMIT, which can be attributed to an enhanced bond disproportionation as revealed by the DFT+U calculations, and a tendency of [011]-oriented films to formation of structural defects and stabilization of nonequilibrium phases. Our results provide insights into the structure-property relationship of a correlated electron system and its evolution at microscopic length scales and give new perspectives for the epitaxial control of macroscopic phases in metal-oxide heterostructures.
CRIS-Team Scopus Importer:2021-05-14

Correction to: A new benchmark of soft X-ray transition energies of Ne, CO2, and SF6: paving a pathway towards ppm accuracy (The European Physical Journal D, (2022), 76, 3, (38), 10.1140/epjd/s10053-022-00355-0) - Stierhof, Jakob; Kuehn, S.; Winter, Michael; Micke, Peter; Steinbruegge, R.; Shah, C.; Hell, N.; Bissinger, Matthias; Hirsch, Maria; Ballhausen, Ralf; Lang, Melanie; Gräfe, Christina; et al. (European Physical Journal D, 2022)
CRIS-Team Scopus Importer:2022-11-11

Determining the crystal-field ground state in rare earth heavy fermion materials using soft-X-ray absorption spectroscopy - Hansmann, Philipp; Severing, A.; Hu, Zhiwei; Haverkort, M. W.; Chang, C. F.; Klein, S.; Tanaka, Arata; Hsieh, H. H.; Lin, H. -J.; Chen, C. T.; Fak, B.; Lejay, P.; et al. (Physical Review Letters, 2008)
We infer that soft-x-ray absorption spectroscopy is a versatile method for the determination of the crystal-field ground state symmetry of rare earth heavy fermion systems, complementing neutron scattering. Using realistic and universal parameters, we provide a theoretical mapping between the polarization dependence of Ce M-4,M-5 spectra and the charge distribution of the Ce 4f states. The experimental resolution can be orders of magnitude larger than the 4f crystal-field splitting itself. To demonstrate the experimental feasibility of the method, we investigated CePd2Si2, thereby settling an existing disagreement about its crystal-field ground state.
CRIS-Team WoS Importer:2020-02-19

Dichotomy between Large Local and Small Ordered Magnetic Moments in Iron-Based Superconductors - Hansmann, Philipp; Arita, Ryotaro; Toschi, Alessandro; Sakai, S.; Sangiovanni, Giorgio; Held, Karsten (Physical Review Letters, 2010)
We study a four-band model for iron-based superconductors within the local density approximation combined with dynamical mean-field theory (LDA + DMFT). This successfully reproduces the results of models which take As p degrees of freedom explicitly into account and has several physical advantages over the standard five d-band model. Our findings reveal that the new superconductors are more strongly correlated than their single-particle properties suggest. Two-particle correlation functions unveil the dichotomy between local and ordered magnetic moments in these systems, calling for further experiments to better resolve the short time scale spin dynamics.
CRIS-Team WoS Importer:2020-02-19

Distinct spin and orbital dynamics in Sr2RuO4 - Suzuki, H.; Wang, L.; Bertinshaw, J.; Strand, H. U.R.; Käser, Stefan; Krautloher, M.; Yang, Z.; Wentzell, N.; Parcollet, O.; Jerzembeck, F.; Kikugawa, N.; Mackenzie, A. P.; et al. (Nature Communications, 2023)
The unconventional superconductor Sr2RuO4 has long served as a benchmark for theories of correlated-electron materials. The determination of the superconducting pairing mechanism requires detailed experimental information on collective bosonic excitations as potential mediators of Cooper pairing. We have used Ru L 3-edge resonant inelastic x-ray scattering to obtain comprehensive maps of the electronic excitations of Sr2RuO4 over the entire Brillouin zone. We observe multiple branches of dispersive spin and orbital excitations associated with distinctly different energy scales. The spin and orbital dynamical response functions calculated within the dynamical mean-field theory are in excellent agreement with the experimental data. Our results highlight the Hund metal nature of Sr2RuO4 and provide key information for the understanding of its unconventional superconductivity.
CRIS-Team Scopus Importer:2023-11-17

Effective crystal field and Fermi surface topology: A comparison of d- and dp-orbital models - Parragh, N.; Sangiovanni, Giorgio; Hansmann, Philipp; Hummel, S.; Held, Karsten; Toschi, Alessandro (Physical Review B, 2013)
The effective crystal field in multiorbital correlated materials can be either enhanced or reduced by electronic correlations with crucial consequences for the topology of the Fermi surface and, hence, on the physical properties of these systems. In this respect, recent local density approximation plus dynamical mean-field theory studies of Ni-based heterostructure have shown contradicting results, depending on whether the less correlated p orbitals are included or not. We investigate the origin of this problem and identify the key parameters controlling the Fermi surface properties of these systems. Without the p orbitals, the model is quarter-filled, while the d manifold moves rapidly towards half-filling when the p orbitals are included. This implies that the local Hund's exchange, while rather unimportant for the former case, can play a predominant role in controlling the orbital polarization for the extended basis set by favoring the formation of a larger local magnetic moment.
CRIS-Team WoS Importer:2020-02-19

Electronic correlations in V2O3 studied with K-edge X-ray absorption spectroscopy - Rodolakis, Fanny; Hansmann, Philipp; Rueff, J-P; Toschi, Alessandro; Haverkort, M. W.; Sangiovanni, G.; Held, K.; Sikora, Marcin; Congeduti, A.; Itie, J-P; Baudelet, F.; Metcalf, P.; et al. (14TH INTERNATIONAL CONFERENCE ON X-RAY ABSORPTION FINE STRUCTURE (XAFS14), PROCEEDINGS, 2009)
CRIS-Team WoS Importer:2020-02-19

Electronic response of a Mott insulator at a current-induced insulator-to-metal transition - Suen, C. T.; Marković, I.; Zonno, M.; Heinsdorf, N.; Zhdanovich, S.; Jo, N. H.; Schmid, M.; Hansmann, Philipp; Puphal, P.; Fürsich, K.; Smit, S.; Au-Yeung, C.; et al. (Nature Physics, 2024)
The Mott insulator Ca2RuO4 exhibits an insulator-to-metal transition induced by d.c. current. Despite the thorough examination of the structural changes associated with this transition, a comprehensive knowledge of the response of electronic degrees of freedom is still lacking. Here we demonstrate current-induced modifications of the electronic states of Ca2RuO4. Angle-resolved photoemission spectroscopy in conjunction with four-probe electrical transport (transport-ARPES) measurements reveal a clear reduction of the Mott gap and a modification in the dispersion of the Ru bands. Based on a free-energy analysis, we show that the current-induced phase is electronically distinct from the high-temperature zero-current metallic phase. Our results highlight strong interplay of lattice- and orbital-dependent electronic responses in the current-driven insulator-to-metal transition.
CRIS-Team Scopus Importer:2024-10-18

Electronic structure of nickelates: From two-dimensional heterostructures to three-dimensional bulk materials - Hansmann, Philipp; Toschi, Alessandro; Yang, Xiaoping; Andersen, O. K.; Held, Karsten (Physical Review B, 2010)
Reduced dimensionality and strong electronic correlations, which are among the most important ingredients for cupratelike high-T-c superconductivity, characterize also the physics of nickelate-based heterostructures. Starting from the local-density approximation we arrive at a simple two-band model for quasi-two-dimensional (2D) LaNiO3/LaAlO3 heterostructures and extend it by introducing an appropriate hopping in the z direction to describe the dimensional crossover to three dimensions (3D). Using dynamical mean-field theory, we study the effects of electronic correlations with increasing interaction strength along the crossover from 2D to 3D. Qualitatively, the effects of electronic correlations are surprisingly similar, albeit quantitatively larger interaction strengths are required in three dimensions for getting a Mott-Hubbard insulating state. The exchange parameters of an effective Kugel-Khomskii-type spin-orbital model are also derived and reveal strong antiferromagnetic tendencies.
CRIS-Team WoS Importer:2020-02-19

Evolution of the electronic structure of a Mott system across its phase diagram: X-ray absorption spectroscopy study of (V1-xCrx)(2)O-3 - Rodolakis, Fanny; Rueff, J. -P.; Sikora, Marcin; Alliot, I.; Itie, J. -P.; Baudelet, F.; Ravy, Sylvain; Wzietek, Pawel; Hansmann, Philipp; Toschi, Alessandro; Haverkort, M. W.; Sangiovanni, Giorgio; et al. (Physical Review B, 2011)
V2O3 is an archetypal system for the study of correlation-induced, Mott-Hubbard metal-insulator transitions. Despite decades of extensive investigations, the accurate description of its electronic properties remains an open problem in the physics of strongly correlated materials, also because of the lack of detailed experimental data on its electronic structure over the whole phase diagram. We present here a high-resolution x-ray absorption spectroscopy study at the V K edge of (V1-xCrx)(2)O-3 to probe its electronic structure as a function of temperature, doping, and pressure, providing an accurate picture of the electronic changes over the whole phase diagram. We also discuss the relevance of the parallel evolution of the lattice parameters, determined with x-ray diffraction. This allows us to draw two conclusions of general interest: First, the transition under pressure presents peculiar properties, related to a more continuous evolution of the lattice and electronic structure; second, the lattice mismatch is a good parameter describing the strength of the first-order transition, and is consequently related to the tendency of the system toward the coexistence of different phases. Our results show that the evolution of the electronic structure while approaching a phase transition, and not only while crossing it, is also a key element to unveil the underlying physical mechanisms of Mott materials.
CRIS-Team WoS Importer:2020-02-19

Excitonic magnetism at the intersection of spin-orbit coupling and crystal-field splitting - Feldmaier, Teresa; Strobel, Pascal; Schmid, Michael; Hansmann, Philipp; Daghofer, Maria (Physical Review Research, 2020)
Excitonic magnetism involving superpositions of singlet and triplet states is expected to arise for two holes in strongly correlated and spin-orbit-coupled t(2g) orbitals. However, uncontested material examples for its realization are rare. We apply the variational cluster approach to the square lattice to investigate excitonic antiferromagnetism and the impact of a crystal field. We give a phase diagram depending on spin-orbit coupling and crystal field and find excitonic magnetism to survive in the presence of substantial crystal-field-induced orbital order. We address the specific example of Ca2RuO4 using ab initio modeling and conclude it to realize such excitonic magnetism despite its pronounced orbital polarization. We also reproduce magnetic excitations and show the maximum at momentum (0,0) to be related to the excitonic character of the magnetic order.
CRIS-Team WoS Importer:2021-01-22

Exploring small energy scales with x-ray absorption and dichroism - Praetorius, C.; Zinner, M.; Hansmann, Philipp; Haverkort, M. W.; Fauth, Kai (Physical Review B, 2016)
Soft x-ray linear and circular dichroism (XLD, XMCD) experiments at the Ce M-4,M-5 edges are being used to determine the energy scales characterizing the Ce 4f degrees of freedom in the ultrathin ordered surface intermetallic CeAgx/Ag(111). We find that all relevant interactions, i.e., Kondo scattering, crystal field splitting and magnetic exchange coupling occur on small scales. Our study demonstrates the usefulness of combining x-ray absorption experiments probing the temperature dependence of both linear and circular dichroism owing to their strong sensitivity for anisotropies in both charge distribution and paramagnetic response, respectively.
CRIS-Team WoS Importer:2020-02-19

From antiferromagnetic and hidden order to Pauli paramagnetism in UM2Si2 compounds with 5f electron duality - Amorese, Andrea; Sundermann, Martin; Leedahl, Brett; Marino, Andrea; Takegami, Daisuke; Gretarsson, Hlynur; Gloskovskii, Andrei; Schlueter, Christoph; Haverkort, Maurits W.; Huang, Yingkai; Szlawska, Maria; Kaczorowski, Dariusz; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Using inelastic X-ray scattering beyond the dipole limit and hard X-ray photoelectron spectroscopy we establish the dual nature of the U [Formula: see text] electrons in U[Formula: see text] (M = Pd, Ni, Ru, Fe), regardless of their degree of delocalization. We have observed that the compounds have in common a local atomic-like state that is well described by the U [Formula: see text] configuration with the [Formula: see text] and [Formula: see text] quasi-doublet symmetry. The amount of the U 5[Formula: see text] configuration, however, varies considerably across the U[Formula: see text] series, indicating an increase of U 5f itineracy in going from M = Pd to Ni to Ru and to the Fe compound. The identified electronic states explain the formation of the very large ordered magnetic moments in [Formula: see text] and [Formula: see text], the availability of orbital degrees of freedom needed for the hidden order in [Formula: see text] to occur, as well as the appearance of Pauli paramagnetism in [Formula: see text] A unified and systematic picture of the U[Formula: see text] compounds may now be drawn, thereby providing suggestions for additional experiments to induce hidden order and/or superconductivity in U compounds with the tetragonal body-centered [Formula: see text] structure.
CRIS-Team Scopus Importer:2020-12-11
Keywords: hidden order; strongly correlated electron systems; uranium heavy fermions; X-ray spectroscopy

Importance of d-p Coulomb interaction for high T-C cuprates and other oxides - Hansmann, Philipp; Parragh, N.; Toschi, Alessandro; Sangiovanni, Giorgio; Held, Karsten (New Journal of Physics, 2014)
Current theoretical studies of electronic correlations in transition metal oxides typically only account for the local repulsion between d-electrons even if oxygen ligand p-states are an explicit part of the effective Hamiltonian. Interatomic interactions such as U-pd between d- and (ligand) p-electrons, as well as the local interaction between p-electrons, are neglected. Often, the relative d-p orbital splitting has to be adjusted 'ad hoc' on the basis of the experimental evidence. By applying the merger of local density approximation and dynamical mean field theory to the prototypical case of the three-band Emery dp model for the cuprates, we demonstrate that, without any 'ad hoc' adjustment of the orbital splitting, the charge transfer insulating state is stabilized by the interatomic interaction U-pd. Our study hence shows how to improve realistic material calculations that explicitly include the p-orbitals.
CRIS-Team WoS Importer:2020-02-19

Inequivalent Routes across the Mott Transition in V2O3 Explored by X-Ray Absorption - Rodolakis, Fanny; Hansmann, Philipp; Rueff, J. -P.; Toschi, Alessandro; Haverkort, M. W.; Sangiovanni, Giorgio; Tanaka, A.; Saha-Dasgupta, T.; Andersen, O. K.; Held, Karsten; Sikora, Marcin; Alliot, I.; et al. (Physical Review Letters, 2010)
The changes in the electronic structure of V2O3 across the metal-insulator transition induced by temperature, doping, and pressure are identified using high resolution x-ray absorption spectroscopy at the V pre-K edge. Contrary to what has been taken for granted so far, the metallic phase reached under pressure is shown to differ from the one obtained by changing doping or temperature. Using a novel computational scheme, we relate this effect to the role and occupancy of the a(1g) orbitals. This finding unveils the inequivalence of different routes across the Mott transition in V2O3.
CRIS-Team WoS Importer:2020-02-19

Interorbital singlet pairing in Sr2RuO4: A Hund's superconductor - Käser, Stefan; Strand, Hugo U.R.; Wentzell, Nils; Georges, Antoine; Parcollet, Olivier; Hansmann, Philipp (Physical Review B, 2022)
We study the superconducting gap function of Sr2RuO4. By solving the linearized Eliashberg equation with a correlated pairing vertex extracted from a dynamical mean-field calculation we identify the dominant pairing channels. An analysis of the candidate gap functions in orbital and quasiparticle band basis reveals that an interorbital singlet pairing of even parity is in agreement with experimental observations. It reconciles in particular the occurrence of a two-component order parameter with the presence of line nodes of quasiparticles along the c axis in the superconducting phase. The strong angular dependence of the gap along the Fermi surface is in stark contrast to its quasilocality when expressed in the orbital basis. We identify local interorbital spin correlations as the driving force for the pairing and thus reveal the continuation of Hund's physics into the superconducting phase.
CRIS-Team Scopus Importer:2022-04-29

Long-Range Coulomb Interactions in Surface Systems: A First-Principles Description within Self-Consistently Combined GW and Dynamical Mean-Field Theory - Hansmann, Philipp; Ayral, Thomas; Vaugier, L.; Werner, Philipp; Biermann, Silke (Physical Review Letters, 2013)
Systems of adatoms on semiconductor surfaces display competing ground states and exotic spectral properties typical of two-dimensional correlated electron materials which are dominated by a complex interplay of spin and charge degrees of freedom. We report a fully ab initio derivation of low-energy Hamiltonians for the adatom systems Si(111) : X, with X = Sn, Si, C, Pb, that we solve within self-consistently combined GW and dynamical mean-field theory. Calculated photoemission spectra are in agreement with available experimental data. We rationalize experimentally observed trends from Mott physics toward charge ordering along the series as resulting from substantial long-range interactions. DOI: 10.1103/PhysRevLett.110.166401
CRIS-Team WoS Importer:2020-02-19

Magnetic correlations in infinite-layer nickelates: An experimental and theoretical multimethod study - Ortiz, R. A.; Puphal, P.; Klett, M.; Hotz, F.; Kremer, R. K.; Trepka, H.; Hemmida, M.; Von Nidda, H-A Krug; Isobe, M.; Khasanov, R.; Luetkens, H.; Hansmann, Philipp; et al. (Physical Review Research, 2022)
We report a comprehensive study of magnetic correlations in LaNiO2, a parent compound of the recently discovered family of infinite-layer (IL) nickelate superconductors, using multiple experimental and theoretical methods. Our specific heat, muon-spin rotation (µSR), and magnetic susceptibility measurements on polycrystalline LaNiO2 show that long-range magnetic order remains absent down to 2 K. Nevertheless, we detect residual entropy in the low-temperature specific heat, which is compatible with a model fit that includes paramagnon excitations. The µSR and low-field static and dynamic magnetic susceptibility measurements indicate the presence of short-range magnetic correlations and glassy spin dynamics, which we attribute to local oxygen nonstoichiometry in the average infinite-layer crystal structure. This glassy behavior can be suppressed in strong external fields, allowing us to extract the intrinsic paramagnetic susceptibility. Remarkably, we find that the intrinsic susceptibility shows non-Curie-Weiss behavior at high temperatures, in analogy to doped cuprates that possess robust nonlocal spin fluctuations. The distinct temperature dependence of the intrinsic susceptibility of LaNiO2 can be theoretically understood by a multimethod study of the single-band Hubbard model in which we apply complementary cutting-edge quantum many-body techniques (dynamical mean-field theory, cellular dynamical mean-field theory, and the dynamical vertex approximation) to investigate the influence of both short- and long-ranged correlations. Our results suggest a profound analogy between the magnetic correlations in parent (undoped) IL nickelates and doped cuprates.
CRIS-Team Scopus Importer:2022-06-10

Magnetic Properties and Pseudogap Formation in Infinite-Layer Nickelates: Insights From the Single-Band Hubbard Model - Klett, Marcel; Hansmann, Philipp; Schäfer, Thomas (Frontiers in Physics, 2022)
We study the magnetic and spectral properties of a single-band Hubbard model for the infinite-layer nickelate compound LaNiO2. As spatial correlations turn out to be the key ingredient for understanding its physics, we use two complementary extensions of the dynamical mean-field theory to take them into account: the cellular dynamical mean-field theory and the dynamical vertex approximation. Additionally to the systematic analysis of the doping dependence of the non-Curie-Weiss behavior of the uniform magnetic susceptibility, we provide insight into its relation to the formation of a pseudogap regime by the calculation of the one-particle spectral function and the magnetic correlation length. The latter is of the order of a few lattice spacings when the pseudogap opens, indicating a strong-coupling pseudogap formation in analogy to cuprates.
CRIS-Team Scopus Importer:2022-03-18
Keywords: cellular dynamical mean field theory; dynamical mean-field theory (DMFT); dynamical vertex approximation; hubbard model; magnetism; nickelates; pseudogap

Mechanism of charge transfer/disproportionation in LnCu(3)Fe(4)O(12) (Ln = lanthanides) - Rezaei, N.; Hansmann, Philipp; Bahramy, M. S.; Arita, Ryotaro (Physical Review B, 2014)
The Fe-Cu intersite charge transfer and Fe charge disproportionation are interesting phenomena observed in some LnCu(3)Fe(4)O(12) (Ln = lanthanides) compounds containing light and heavy Ln atoms, respectively. We show that a change in the spin state is responsible for the intersite charge transfer in the light Ln compounds. At the high-spin state, such systems prefer an unusual Cu d(8) configuration, whereas at the low-spin state they retreat to the normal Cu d(9) configuration through a charge transfer from Fe to the Cu 3d(xy) orbital. We find that the strength of the crystal-field splitting and the relative energy ordering between Cu 3d(xy) and Fe 3d states are the key parameters determining the intersite charge transfer (charge disproportionation) in light (heavy) Ln compounds. It is further proposed that the size of Ln affects the on-site interaction strength of Cu 3d states, leading to a strong modification of the Cu L-3-edge spectrum, as observed by the x-ray-absorption spectroscopy.
CRIS-Team WoS Importer:2020-02-19

Mott-Hubbard transition in V2O3 revisited - Hansmann, Philipp; Toschi, Alessandro; Sangiovanni, Giorgio; Saha-Dasgupta, T.; Lupi, S.; Marsi, Marino; Held, Karsten (physica status solidi (b), 2013)
The isostructural metal-insulator transition in Cr-doped V2O3 is the textbook example of a Mott-Hubbard transition between a paramagnetic metal (PM) and a paramagnetic insulator. We review recent theoretical calculations as well as experimental findings which shed new light on this famous transition. In particular, the old paradigm of a doping-pressure equivalence does not hold, and there is a microscale phase separation for Cr-doped V2O3. (C) 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
CRIS-Team WoS Importer:2020-02-19

Mott Insulating States with Competing Orders in the Triangular Lattice Hubbard Model - Wietek, Alexander; Rossi, Riccardo; Simkovic, Fedor; Klett, Marcel; Hansmann, Philipp; Ferrero, Michel; Stoudenmire, E. Miles; Schaefer, Thomas; Georges, Antoine (Physical Review X, 2021)
The physics of the triangular lattice Hubbard model exhibits a rich phenomenology, ranging from a metal-insulator transition, intriguing thermodynamic behavior, and a putative spin liquid phase at intermediate coupling, ultimately becoming a magnetic insulator at strong coupling. In this multimethod study, we combine a finite-temperature tensor network method, minimally entangled thermal typical states (METTS), with two Green-function-based methods, connected-determinant diagrammatic Monte Carlo and cellular dynamical mean-field theory, to establish several aspects of this model. We elucidate the evolution from the metallic to the insulating regime from the complementary perspectives brought by these different methods. We compute the full thermodynamics of the model on a width-four cylinder using METTS in the intermediate to strong coupling regime. We find that the insulating state hosts a large entropy at intermediate temperatures, which increases with the strength of the coupling. Correspondingly, and consistently with a thermodynamic Maxwell relation, the double occupancy has a minimum as a function of temperature which is the manifestation of the Pomeranchuk effect of increased localization upon heating. The intermediate coupling regime is found to exhibit both pronounced chiral as well as stripy antiferromagnetic spin correlations. We propose a scenario in which time-reversal symmetry-broken states compete with stripy-spin states at lowest temperatures.
CRIS-Team WoS Importer:2021-10-29

Mott insulators with boundary zeros - Wagner, N.; Crippa, L.; Amaricci, A.; Hansmann, Philipp; Klett, M.; König, E. J.; Schäfer, T.; Sante, D. Di; Cano, J.; Millis, A. J.; Georges, A.; Sangiovanni, G. (Nature Communications, 2023)
The topological classification of electronic band structures is based on symmetry properties of Bloch eigenstates of single-particle Hamiltonians. In parallel, topological field theory has opened the doors to the formulation and characterization of non-trivial phases of matter driven by strong electron-electron interaction. Even though important examples of topological Mott insulators have been constructed, the relevance of the underlying non-interacting band topology to the physics of the Mott phase has remained unexplored. Here, we show that the momentum structure of the Green’s function zeros defining the “Luttinger surface" provides a topological characterization of the Mott phase related, in the simplest description, to the one of the single-particle electronic dispersion. Considerations on the zeros lead to the prediction of new phenomena: a topological Mott insulator with an inverted gap for the bulk zeros must possess gapless zeros at the boundary, which behave as a form of “topological antimatter” annihilating conventional edge states. Placing band and Mott topological insulators in contact produces distinctive observable signatures at the interface, revealing the otherwise spectroscopically elusive Green’s function zeros.
CRIS-Team Scopus Importer:2023-12-15

Mott transition and pseudogap of the square-lattice Hubbard model: Results from center-focused cellular dynamical mean-field theory - Meixner, Michael; Menke, Henri; Klett, Marcel; Heinzelmann, Sarah; Andergassen, Sabine; Hansmann, Philipp; Schäfer, Thomas (SciPost Physics, 2024)
The recently proposed center-focused post-processing procedure [Phys. Rev. Res. 2, 033476 (2020)] of cellular dynamical mean-field theory suggests that central sites of large impurity clusters are closer to the exact solution of the Hubbard model than the edge sites. In this paper, we systematically investigate results in the spirit of this center-focused scheme for several cluster sizes up to 8 × 8 in and out of particle-hole symmetry. First we analyze the metal-insulator crossovers and transitions of the half-filled Hubbard model on a simple square lattice. We find that the critical interaction of the crossover is reduced with increasing cluster sizes and the critical temperature abruptly drops for the 4 × 4 cluster. Second, for this cluster size, we apply the center-focused scheme to a system with more realistic tight-binding parameters, investigating its pseudogap regime as a function of temperature and doping, where we find doping dependent metal-insulator crossovers, Lifshitz transitions and a strongly renormalized Fermi-liquid regime. Additionally to diagnosing the real space origin of the suppressed antinodal spectral weight in the pseudogap regime, we can infer hints towards underlying charge ordering tendencies.
CRIS-Team Scopus Importer:2024-05-03

Multiferroic properties of melanothallite Cu2OCl2 - Guo, H.; Zhao, L.; Schmidt, W.; Fernandez-Diaz, M. T.; Becker, Ch; Melendez-Sans, A.; Peng, W.; Zbiri, M.; Hansmann, Philipp; Komarek, A. C. (Physical Review Materials, 2019)
Here we report on P-E hysteresis loop measurements that unravel the ferroelectric nature of melanothallite Cu2OCl2, a new multiferroic material with high critical temperature. Its spin structure was investigated by polarized and unpolarized neutron scattering experiments which reveal a cycloidal magnetic structure with vector chirality (magnetic polarity) that can be inverted by opposite poling of the sample with an inverted electric field. This shows that Cu2OCl2 is a spin-induced ferroelectric material. Finally, we show that the ferroelectric properties of Cu2OCl2 are driven by the inverse Dzyaloshinskii-Moriya interaction mechanism which is also able to predict the observed direction of the ferroelectric polarization properly. The origin of the noncollinear spin structure in melanothallite are competing AFM-FM exchange couplings which we estimate from a combined ab initio + cluster configuration interaction calculation.
CRIS-Team Scopus Importer:2020-02-19

Natural-orbital impurity solver and projection approach for Green's functions - Lu, Y.; Cao, X.; Hansmann, Philipp; Haverkort, M. W. (Physical Review B, 2019)
We extend a previously proposed rotation and truncation scheme to optimize quantum Anderson impurity calculations with exact diagonalization [Y. Lu, M. Höppner, O. Gunnarsson, and M. W. Haverkort, Phys. Rev. B 90, 085102 (2014)PRBMDO1098-012110.1103/PhysRevB.90.085102] to density-matrix renormalization group (DMRG) calculations. The method reduces the solution of a full impurity problem with virtually unlimited bath sites to that of a small subsystem based on a natural impurity orbital basis set. The later is solved by DMRG in combination with a restricted-active-space truncation scheme. The method allows one to compute Green's functions directly on the real frequency or time axis. We critically test the convergence of the truncation scheme using a one-band Hubbard model solved in the dynamical mean-field theory. The projection is exact in the limit of both infinitely large and small Coulomb interactions. For all parameter ranges, the accuracy of the projected solution converges exponentially to the exact solution with increasing subsystem size.
CRIS-Team Scopus Importer:2020-02-19

Orbital characters of three-dimensional Fermi surfaces in Eu2-xSrxNiO4 as probed by soft-x-ray angle-resolved photoemission spectroscopy - Uchida, Masaki; Ishizaka, Kyoko; Hansmann, Philipp; Yang, Xiaoping; Sakano, M.; Miyawaki, J.; Arita, Ryotaro; Kaneko, Yoshio; Takata, Y.; Oura, Masaki; Toschi, Alessandro; Held, Karsten; et al. (Physical Review B, 2011)
The three-dimensional Fermi-surface structure of hole-doped metallic layered nickelate Eu2-xSrxNiO4 (x = 1.1), an important counterpart to the isostructural superconducting cuprate La2-xSrxCuO4, is investigated by energy-dependent soft-x-ray angle-resolved photoemission spectroscopy. In addition to a large cylindrical hole Fermi surface analogous to the cuprates, we observe a Gamma-centered 3z(2) - r(2)-derived small electron pocket. This finding demonstrates that in the layered nickelate the 3z(2) - r(2) band resides close to the x(2) - y(2) one in energy. The resultant multiband feature with varying orbital character as revealed may strongly work against the emergence of the high-temperature superconductivity.
CRIS-Team WoS Importer:2020-02-19

Orbital selective coupling in CeRh3 B2: Coexistence of high Curie and high Kondo temperatures - Amorese, Andrea; Hansmann, Philipp; Marino, Andrea; Körner, Peter; Willers, Thomas; Walters, Andrew; Zhou, Ke Jin; Kummer, Kurt; Brookes, Nicholas B.; Lin, Hong Ji; Chen, Chien Te; Lejay, Pascal; et al. (Physical Review B, 2023)
We investigated the electronic structure of the enigmatic CeRh3B2 using resonant inelastic scattering and x-ray absorption spectroscopy in combination with ab initio density functional calculations. We find that the Rh4d states are irrelevant for the high-temperature ferromagnetism and the Kondo effect. We also find that the Ce4f crystal-field strength is too small to explain the strong reduction of the Ce magnetic moment. The data revealed instead the presence of two different active Ce4f orbitals, with each coupling selectively to different bands in CeRh3B2. The intersite hybridization of the |J=52,Jz=±12) crystal-field state and Ce5d band combined with the intrasite Ce4f-5d exchange creates the strong ferromagnetism, while hybridization between the |J=52,Jz=±52) and the B sp in the ab-plane contributes to the Kondo interaction, which causes the moment reduction. This orbital selective coupling explains the unique and seemingly contradictory properties of CeRh3B2.
CRIS-Team Scopus Importer:2023-04-21

Origins of bond and spin order in rare-earth nickelate bulk and heterostructures - Lu, Yi; Zhong, Zhicheng; Haverkort, Maurits W.; Hansmann, Philipp (Physical Review B, 2017)
We analyze the charge- and spin-response functions of rare-earth nickelates RNiO3 and their heterostructures using random-phase approximation in a two-band Hubbard model. The interorbital charge fluctuation is found to be the driving mechanism for the rock-salt-type bond order in bulk RNiO3, and good agreement of the ordering temperature with experimental values is achieved for all RNiO3 using realistic crystal structures and interaction parameters. We further show that magnetic ordering in bulk is not driven by the spin fluctuation and should be instead explained as ordering of localized moments. This picture changes for low-dimensional heterostructures, where the charge fluctuation is suppressed and overtaken by the enhanced spin instability, which results in a spin-density-wave ground state observed in recent experiments. Predictions for spectroscopy allow for further experimental testing of our claims.
CRIS-Team WoS Importer:2020-02-19

Oxygen sublattice disorder and valence state modulation in infinite-layer nickelate superlattices - Ortiz, R. A.; Enderlein, Niklas; Fürsich, K.; Pons, R.; Radhakrishnan, P.; Schierle, E.; Wochner, P.; Logvenov, G.; Cristiani, G.; Hansmann, Philipp; Keimer, B.; Benckiser, E. (Physical Review Materials, 2025)
The family of infinite-layer nickelates promises important insights into the mechanism of unconventional superconductivity. Since superconductivity has so far only been observed in epitaxial thin films, heteroepitaxy with the substrate or a capping layer possibly plays an important role. Here, we use soft x-ray spectroscopy to investigate superlattices as a potential approach for a targeted material design of high-temperature superconductors. We observe modulations in valence state and oxygen coordination in topotactically reduced artificial superlattices with repeating interfaces between nickelate layers and layers of materials commonly used as substrates and capping layers. Our results show that depending on the interlayer material metallic conductivity akin to the parent infinite-layer compounds is achieved. Depth-resolved electronic structure measured by resonant x-ray reflectivity reveals a reconstructed ligand field and valence state at the interface, which is confined to one or two unit cells. The central layers are predominantly monovalent nickel, but linear dichroism analysis reveals considerable disorder in the oxygen removal sites. We observe a quantitative correlation of this disorder with the interlayer material that is important for future modeling and design strategies.
CRIS-Team Scopus Importer:2025-06-06

Pressure and alloying effects on the metal to insulator transition in NiS2-xSex studied by infrared spectroscopy - Perucchi, A.; Marini, C.; Valentini, Matteo; Postorino, P.; Sopracase, R.; Dore, Paolo; Hansmann, Philipp; Jepsen, O.; Sangiovanni, Giorgio; Toschi, Alessandro; Held, Karsten; Topwal, D.; et al. (Physical Review B, 2009)
The metal to insulator transition in the charge-transfer NiS2-xSex compound has been investigated through infrared reflectivity. Measurements performed by applying pressure to pure NiS2 (lattice contraction) and by Se alloying (lattice expansion) reveal that in both cases an anomalous metallic state is obtained. We find that optical results are not compatible with the linear Se-alloying vs pressure-scaling relation previously established through transport, thus pointing out the substantially different microscopic origin of the two transitions.
CRIS-Team WoS Importer:2020-02-19

Pseudogap of Metallic Layered Nickelate R2-xSrxNiO4 (R = Nd, Eu) Crystals Measured Using Angle-Resolved Photoemission Spectroscopy - Uchida, Masaki; Ishizaka, Kyoko; Hansmann, Philipp; Kaneko, Yoshio; Ishida, Yukiaki; Yang, Xiaoping; Kumai, Reiji; Toschi, Alessandro; Onose, Yoshinori; Arita, Ryotaro; Held, Karsten; Andersen, O. K.; et al. (Physical Review Letters, 2011)
We have investigated charge dynamics and electronic structures for single crystals of metallic layered nickelates, R2-xSrxNiO4 (R = Nd, Eu), isostructural to La2-xSrxCuO4. Angle-resolved photoemission spectroscopy on the barely metallic Eu0.9Sr1.1NiO4 (R = Eu, x = 1.1) has revealed a large hole surface of x(2) - y(2) character with a high-energy pseudogap of the same symmetry and comparable magnitude with those of underdoped (x < 0.1) cuprates, although the antiferromagnetic interactions are 1 order of magnitude smaller. This finding strongly indicates that the momentum-dependent pseudogap feature in the layered nickelate arises from the real-space charge correlation.
CRIS-Team WoS Importer:2020-02-19

Quantum dynamical screening of the local magnetic moment in Fe-based superconductors - Toschi, Alessandro; Arita, Ryotaro; Hansmann, Philipp; Sangiovanni, Giorgio; Held, Karsten (Physical Review B, 2012)
We have calculated the local magnetic susceptibility of one of the prototypical Fe-based superconductors (LaFeAsO) by means of the local density approximation + dynamical mean field theory as a function of both (imaginary) time and real frequencies with and without vertex corrections. Vertex corrections are essential for obtaining the correct omega dependence, in particular, a pronounced low-energy peak at omega similar to 0.2 eV, which constitutes the hallmark of the dynamical screening of a large instantaneous magnetic moment on the Fe atoms. In experiments, however, except for the case of x-ray absorption spectroscopy, the magnetic moment or the susceptibility represent typically the average over long time scales. In this respect, the frequency range of typical neutron experiments would be too limited to directly estimate the magnitude of the short-time moment.
CRIS-Team WoS Importer:2020-02-19

Real-space cluster dynamical mean-field theory: Center-focused extrapolation on the one- and two particle-levels - Klett, Marcel; Wentzell, Nils; Schafer, Thomas; Simkovic, Fedor; Parcollet, Olivier; Andergassen, Sabine; Hansmann, Philipp (Physical Review Research, 2020)
We revisit the cellular dynamical mean-field theory (CDMFT) for the single-band Hubbard model on the square lattice at half filling, reaching real-space cluster sizes of up to 9 x 9 sites. Using benchmarks against direct lattice diagrammatic Monte Carlo at high temperature, we show that the self-energy obtained from a cluster center-focused extrapolation converges faster with the cluster size than the periodization schemes previously introduced in the literature. The same benchmark also shows that the cluster spin susceptibility can be extrapolated to the exact result at large cluster size, even though its spatial extension is larger than the cluster size.
CRIS-Team WoS Importer:2021-01-22

Single-particle spectra and magnetic susceptibility in the Emery model: A dynamical mean-field perspective - Tseng, Yi-Ting; Malcolms, Mário O.; Menke, Henri; Klett, Marcel; Schäfer, Thomas; Hansmann, Philipp (SciPost Physics, 2025)
We investigate dynamical mean-field calculations of the three-band Emery model at the one- and two-particle level for material-realistic parameters of high-Tc superconductors. Our study shows that even within dynamical mean-field theory, which accounts solely for temporal fluctuations, the intrinsic multi-orbital nature of the Emery model introduces effective non-local correlations. These correlations lead to a non-Curie-like temperature dependence of the magnetic susceptibility, consistent with nuclear magnetic resonance experiments in the pseudogap regime. By analyzing the temperature dependence of the uniform static spin susceptibility obtained by single-site and cluster dynamical mean-field theory, we find indications of emerging oxygen-copper singlet fluctuations, explicitly captured by the model. Despite correctly describing the hallmark of the pseudogap at the two-particle level, such as the drop in the Knight shift of nuclear magnetic resonance, dynamical mean-field theory fails to capture the spectral properties of the pseudogap.
CRIS-Team Scopus Importer:2025-05-16

Spectral properties of the Mott Hubbard insulator (Cr0.011V0.989)(2)O-3 calculated by LDA plus DMFT - Toschi, Alessandro; Hansmann, Philipp; Sangiovanni, Giorgio; Saha-Dasgupta, T.; Andersen, O. K.; Held, Karsten (INTERNATIONAL CONFERENCE ON MAGNETISM (ICM 2009), 2010)
Significant progress in the theoretical description of Mott-Hubbard metal-to-insulator transitions has been made in the last years, especially thanks to the LDA+DMFT approach (local density approximation + dynamical mean field theory). Obviously the main attention has been focused on the transition itself, as, for example, in the textbook case of the Cr-doped V2O3. As we discuss here, however, also the study of the insulating phase, characterized by the opening of a visible Mott-Hubbard gap in the spectral functions is far from being trivial: Strong-correlation effects make this phase strongly sensitive to small changes of external parameters, much more than one would expect for an insulator. In this situation, requiring a full consistency of the theoretical calculations with data from different spectroscopies may provide the most precise estimate for the local Coulomb interaction U in the LDA+DMFT approach.
CRIS-Team WoS Importer:2020-02-19

Superlattice approach to doping infinite-layer nickelates - Ortiz, R. A.; Menke, Henri; Misjak, F.; Mantadakis, D. T.; Fuersich, K.; Schierle, E.; Logvenov, G.; Kaiser, U.; Keimer, B.; Hansmann, Philipp; Benckiser, E. (Physical Review B, 2021)
The recent observation of superconductivity in infinite-layer Nd1-xSrxNiO2 thin films has attracted a lot of attention, since this compound is electronically and structurally analogous to the superconducting cuprates. Due to the challenges in the phase stabilization upon chemical doping with Sr, we synthesized artificial superlattices of LaNiO3 embedded in insulating LaGaO3, and we used layer-selective topotactic reactions to reduce the nickelate layers to LaNiO2. Hole doping is achieved via interfacial oxygen atoms and tuned via the layer thickness. We used electrical transport measurements, transmission electron microscopy, and x-ray spectroscopy together with ab initio calculations to track changes in the local nickel electronic configuration upon reduction, and we found that these changes are reversible. Our experimental and theoretical data indicate that the doped holes are trapped at the interfacial quadratic pyramidal Ni sites. Calculations for electron-doped cases predict a different behavior, with evenly distributed electrons among the layers, thus opening up interesting perspectives for interfacial doping of transition-metal oxides.
CRIS-Team WoS Importer:2021-11-05

Tailoring the structure and thermoelectric properties of BaTiO3 via Eu2+ substitution - Xiao, Xingxing; Widenmeyer, Marc; Xie, Wenjie; Zou, Tianhua; Yoon, Songhak; Scavini, Marco; Checchia, Stefano; Zhong, Zhicheng; Hansmann, Philipp; Kilper, Stefan; Kovalevsky, Andrei; Weidenkaff, Anke (Physical Chemistry Chemical Physics, 2017)
A series of Ba1-xEuxTiO3-delta (0.1 <= x <= 0.9) phases with similar to 40 nm particle size were synthesized via a Pechini method followed by annealing and sintering under a reducing atmosphere. The effects of Eu2+ substitution on the BaTiO3 crystal structure and the thermoelectric transport properties were systematically investigated. According to synchrotron X-ray diffraction data only cubic perovskite structures were observed. On the local scale below about 20 angstrom (equal to similar to 5 unit cells) deviations from the cubic structure model (Pm% (3) over barm) were detected by evaluation of the pair distribution function (PDF). These deviations cannot be explained by a simple symmetry breaking model like in EuTiO3-delta. The best fit was achieved in the space group Amm2 allowing for a movement of Ti and Ba/Eu along < 110 > of the parent unit cell as observed for BaTiO3. Density functional calculations delivered an insight into the electronic structure of Ba1-xEuxTiO3-delta. From the obtained density of states a significant reduction of the band gap by the presence of filled Eu2+ 4f states at the top of the valence band was observed. The physical property measurements revealed that barium-europium titanates exhibit n-type semiconducting behavior and at high temperature the electrical conductivity strongly depended on the Eu2+ content. Activation energies calculated from the electrical conductivity and Seebeck coefficient data indicate that at high temperatures (800 K < T < 1123 K) the conduction mechanism of Ba1-xEuxTiO3-delta (0.1 <= x <= 0.9) is a polaron hopping when 0 <= x <= 0.6 and is a thermally activated process when 0.6 < x < 1. Besides, the thermal conductivity increases with increasing Eu2+ concentration. Due to a remarkable improvement of the power factor, Ba0.1Eu0.9TiO3-delta showed a ZT value of 0.24 at 1123 K.
CRIS-Team WoS Importer:2020-02-19

Theoretical Prediction and Spectroscopic Fingerprints of an Orbital Transition in CeCu2Si2 - Pourovskii, L. V.; Hansmann, Philipp; Ferrero, Michel; Georges, Antoine (Physical Review Letters, 2014)
We show that the heavy-fermion compound CeCu2Si2 undergoes a transition between two regimes dominated by different crystal-field states. At low pressure P and low temperature T the Ce 4f electron resides in the atomic crystal-field ground state, while at high P or T, the electron occupancy and spectral weight is transferred to an excited crystal-field level that hybridizes more strongly with itinerant states. These findings result from first-principles dynamical-mean-field-theory calculations. We predict experimental signatures of this orbital transition in x-ray spectroscopy. The corresponding fluctuations may be responsible for the second high-pressure superconducting dome observed in this and similar materials.
CRIS-Team WoS Importer:2020-02-19

Thickness Dependent Properties in Oxide Heterostructures Driven by Structurally Induced Metal-Oxygen Hybridization Variations - Liao, Zhaoliang; Gauquelin, Nicolas; Green, Robert J.; Macke, Sebastian; Gonnissen, Julie; Thomas, Sean; Zhong, Zhicheng; Li, Lin; Si, Liang; Van Aert, Sandra; Hansmann, Philipp; Held, Karsten; et al. (Advanced Functional Materials, 2017)
Thickness-driven electronic phase transitions are broadly observed in different types of functional perovskite heterostructures. However, uncertainty remains whether these effects are solely due to spatial confinement, broken symmetry, or rather to a change of structure with varying film thickness. Here, this study presents direct evidence for the relaxation of oxygen-2p and Mn-3d orbital (p-d) hybridization coupled to the layer-dependent octahedral tilts within a La2/3Sr1/3MnO3 film driven by interfacial octahedral coupling. An enhanced Curie temperature is achieved by reducing the octahedral tilting via interface structure engineering. Atomically resolved lattice, electronic, and magnetic structures together with X-ray absorption spectroscopy demonstrate the central role of thickness-dependent p-d hybridization in the widely observed dimensionality effects present in correlated oxide heterostructures.
CRIS-Team WoS Importer:2020-02-19

Towards a First-Principles Determination of Effective Coulomb Interactions in Correlated Electron Materials: Role of Intershell Interactions - Seth, Priyanka; Hansmann, Philipp; Van Roekeghem, Ambroise; Vaugier, Loig; Biermann, Silke (Physical Review Letters, 2017)
The determination of the effective Coulomb interactions to be used in low-energy Hamiltonians for materials with strong electronic correlations remains one of the bottlenecks for parameter-free electronic structure calculations. We propose and benchmark a scheme for determining the effective local Coulomb interactions for charge-transfer oxides and related compounds. Intershell interactions between electrons in the correlated shell and ligand orbitals are taken into account in an effective manner, leading to a reduction of the effective local interactions on the correlated shell. Our scheme resolves inconsistencies in the determination of effective interactions as obtained by standard methods for a wide range of materials, and allows for a conceptual understanding of the relation of cluster model and dynamical mean field-based electronic structure calculations.
CRIS-Team WoS Importer:2020-02-19

Tracking the Footprints of Spin Fluctuations: A MultiMethod, MultiMessenger Study of the Two-Dimensional Hubbard Model - Schaefer, Thomas; Wentzell, Nils; Simkovic, Fedor; He, Yuan-Yao; Hille, Cornelia; Klett, Marcel; Eckhardt, Christian J.; Arzhang, Behnam; Harkov, Viktor; Le Regent, Francois-Marie; Kirsch, Alfred; Wang, Yan; et al. (Physical Review X, 2021)
The Hubbard model represents the fundamental model for interacting quantum systems and electronic correlations. Using the two-dimensional half-filled Hubbard model at weak coupling as a testing ground, we perform a comparative study of a comprehensive set of state-of-the-art quantum many-body methods. Upon cooling into its insulating antiferromagnetic ground state, the model hosts a rich sequence of distinct physical regimes with crossovers between a high-temperature incoherent regime, an intermediate-temperature metallic regime, and a low-temperature insulating regime with a pseudogap created by antiferromagnetic fluctuations. We assess the ability of each method to properly address these physical regimes and crossovers through the computation of several observables probing both quasiparticle properties and magnetic correlations, with two numerically exact methods (diagrammatic and determinantal quantumMonte Carlo methods) serving as a benchmark. By combining computational results and analytical insights, we elucidate the nature and role of spin fluctuations in each of these regimes. Based on this analysis, we explain how quasiparticles can coexist with increasingly long-range antiferromagnetic correlations and why dynamical mean-field theory is found to provide a remarkably accurate approximation of local quantities in the metallic regime. We also critically discuss whether imaginary-time methods are able to capture the non-Fermi-liquid singularities of this fully nested system.
CRIS-Team WoS Importer:2021-04-02

Tree tensor-network real-time multiorbital impurity solver: Spin-orbit coupling and correlation functions in Sr2RuO4 - Cao, X.; Lu, Y.; Hansmann, Philipp; Haverkort, M. W. (Physical Review B, 2021)
We present a tree tensor-network impurity solver suited for general multiorbital systems. The network is constructed to efficiently capture the entanglement structure and symmetry of an impurity problem. The solver works directly on the real-time/frequency axis and generates spectral functions with energy-independent resolution of the order of one percent of the correlated bandwidth. Combined with an optimized representation of the impurity bath, it efficiently solves self-consistent dynamical mean-field equations and calculates various dynamical correlation functions for systems with off-diagonal Green's functions. For the archetypal correlated Hund's metal Sr2RuO4, we show that both the low-energy quasiparticle spectra related to the van Hove singularity and the high-energy atomic multiplet excitations can be faithfully resolved. In particular, we show that while the spin-orbit coupling has only minor effects on the orbital-diagonal one-particle spectral functions, it has a more profound impact on the low-energy spin and orbital response functions.
CRIS-Team Scopus Importer:2021-09-24

Tuning the work function in transition metal oxides and their heterostructures - Zhong, Zhicheng; Hansmann, Philipp (Physical Review B, 2016)
The development of novel functional materials in experimental labs combined with computer-based compound simulation brings the vision of materials design on a microscopic scale continuously closer to reality. For many applications interface and surface phenomena rather than bulk properties are key. One of the most fundamental qualities of a material-vacuum interface is the energy required to transfer an electron across this boundary, i. e., the work function. It is a crucial parameter for numerous applications, including organic electronics, field electron emitters, and thermionic energy converters. Being generally very resistant to degradation at high temperatures, transition metal oxides present a promising materials class for such devices. We have performed a systematic study for perovskite oxides that provides reference values and, equally important, reports on materials trends and the tunability of work functions. Our results identify and classify dependencies of the work function on several parameters including specific surface termination, surface reconstructions, oxygen vacancies, and heterostructuring.
CRIS-Team WoS Importer:2020-02-19

Turning a Nickelate Fermi Surface into a Cupratelike One through Heterostructuring - Hansmann, Philipp; Yang, Xiaoping; Toschi, Alessandro; Khaliullin, G.; Andersen, O. K.; Held, Karsten (Physical Review Letters, 2009)
Using the local density approximation and its combination with dynamical mean-field theory, we show that electronic correlations induce a single-sheet, cupratelike Fermi surface for hole-doped 1/1 LaNiO(3)/LaAlO(3) heterostructures, even though both e(g) orbitals contribute to it. The Ni 3d(3z)(2)-1 orbital plays the role of the axial Cu 4s-like orbital in the cuprates. These two results indicate that "orbital engineering" by means of heterostructuring should be possible. As we also find strong antiferromagnetic correlations, the low-energy electronic and spin excitations in nickelate heterostructures resemble those of high-temperature cuprate superconductors.
CRIS-Team WoS Importer:2020-02-19

Uncertainty principle for experimental measurements: Fast versus slow probes - Hansmann, Philipp; Ayral, Thomas; Tejeda, A.; Biermann, Silke (Scientific Reports, 2016)
The result of a physical measurement depends on the time scale of the experimental probe. In solid-state systems, this simple quantum mechanical principle has far-reaching consequences: the interplay of several degrees of freedom close to charge, spin or orbital instabilities combined with the disparity of the time scales associated to their fluctuations can lead to seemingly contradictory experimental findings. A particularly striking example is provided by systems of adatoms adsorbed on semiconductor surfaces where different experiments-angle-resolved photoemission, scanning tunneling microscopy and core-level spectroscopy-suggest different ordering phenomena. Using most recent first principles many-body techniques, we resolve this puzzle by invoking the time scales of fluctuations when approaching the different instabilities. These findings suggest a re-interpretation of ordering phenomena and their fluctuations in a wide class of solid-state systems ranging from organic materials to high-temperature superconducting cuprates.
CRIS-Team WoS Importer:2020-02-19

Unconventional Crystal Structure of the High-Pressure Superconductor La3Ni2 O7 - Puphal, P.; Reiss, P.; Enderlein, Niklas; Wu, Y. M.; Khaliullin, G.; Sundaramurthy, V.; Priessnitz, T.; Knauft, M.; Suthar, A.; Richter, L.; Isobe, M.; Van Aken, P. A.; et al. (Physical Review Letters, 2024)
The discovery of high-temperature superconductivity in La3Ni2O7 at pressures above 14 GPa has spurred extensive research efforts. Yet, fundamental aspects of the superconducting phase, including the possibility of a filamentary character, are currently subjects of controversial debates. Conversely, a crystal structure with NiO6 octahedral bilayers stacked along the c-axis direction was consistently posited in initial studies on La3Ni2O7. Here, we reassess this structure in optical floating zone-grown La3Ni2O7 single crystals that show signs of filamentary superconductivity. Employing scanning transmission electron microscopy and single-crystal x-ray diffraction under high pressures, we observe multiple crystallographic phases in these crystals, with the majority phase exhibiting alternating monolayers and trilayers of NiO6 octahedra, signifying a profound deviation from the previously suggested bilayer structure. Using density functional theory, we disentangle the individual contributions of the monolayer and trilayer structural units to the electronic band structure of La3Ni2O7, providing a firm basis for advanced theoretical modeling and future evaluations of the potential of the monolayer-trilayer structure for hosting superconductivity.
CRIS-Team Scopus Importer:2024-10-25

Unique Crystal Structure of Ca2RuO4 in the Current Stabilized Semimetallic State - Bertinshaw, J.; Gurung, N.; Jorba, P.; Liu, H.; Schmid, M.; Mantadakis, D. T.; Daghofer, Maria; Krautloher, Maximilian Josef; Jain, A.; Ryu, G. H.; Fabelo, O.; Hansmann, Philipp; et al. (Physical Review Letters, 2019)
The electric-current stabilized semimetallic state in the quasi-two-dimensional Mott insulator Ca2RuO4 exhibits an exceptionally strong diamagnetism. Through a comprehensive study using neutron and x-ray diffraction, we show that this nonequilibrium phase assumes a crystal structure distinct from those of equilibrium metallic phases realized in the ruthenates by chemical doping, high pressure, and epitaxial strain, which in turn leads to a distinct electronic band structure. Dynamical mean field theory calculations based on the crystallographically refined atomic coordinates and realistic Coulomb repulsion parameters indicate a semimetallic state with partially gapped Fermi surface. Our neutron diffraction data show that the nonequilibrium behavior is homogeneous, with antiferromagnetic long-range order completely suppressed. These results provide a new basis for theoretical work on the origin of the unusual nonequilibrium diamagnetism in Ca2RuO4.
CRIS-Team Scopus Importer:2020-02-19

What about U on surfaces? Extended Hubbard models for adatom systems from first principles - Hansmann, Philipp; Vaugier, Loig; Jiang, Hong; Biermann, Silke (Journal of Physics: Condensed Matter, 2013)
Electronic correlations together with dimensional constraints lead to some of the most fascinating properties known in condensed matter physics. As possible candidates where these conditions are realized, semiconductor (111) surfaces and adatom systems on surfaces have been under investigation for quite some time. However, state-of-the-art theoretical studies on these materials that include many-body effects beyond the band picture are rare. First principles estimates of inter-electronic Coulomb interactions for the correlated states are missing entirely, and usually these interactions are treated as adjustable parameters. In this work, we report on calculations of the interaction parameters for the group IV surface-adatom systems in the alpha-phase series of Si(111):C, Si, Sn, Pb. For all systems investigated, the inter-electronic Coulomb interactions are indeed large compared to the kinetic energies of the states in question. Moreover, our study reveals that intersite interactions cannot be disregarded. We explicitly construct an extended Hubbard model for the series of group IV surface-adatom systems on silicon, which can be used for further many-body calculations.
CRIS-Team WoS Importer:2020-02-19